2010
DOI: 10.1038/sj.bjc.6605589
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution genomic profiling of human papillomavirus-associated vulval neoplasia

Abstract: BACKGROUND: The incidence of human papillomavirus-associated vulval neoplasia is increasing worldwide; yet the associated genetic changes remain poorly understood. METHODS: We have used single-nucleotide polymorphism microarray analysis to perform the first high-resolution investigation of genome-wide allelic imbalance in vulval neoplasia. Our sample series comprised 21 high-grade vulval intraepithelial neoplasia and 6 vulval squamous cell carcinomas, with paired non-lesional samples used to adjust for normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
2
4
1
Order By: Relevance
“…HPV‐positive VIN VSCC frequently showed chromosome 1 gains (discussed below), chromosome 3q gain, chromosome 4 loss and chromosome 20 gain. In agreement with this, 2 previous studies on HPV‐positive VIN lesions demonstrated frequent gains at chromosome 1pq, 3q, 19, and/or 20q . Gains of chromosome 1pq, 3q, and 20q were also common in HPV‐positive anal intraepithelial neoplasia .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…HPV‐positive VIN VSCC frequently showed chromosome 1 gains (discussed below), chromosome 3q gain, chromosome 4 loss and chromosome 20 gain. In agreement with this, 2 previous studies on HPV‐positive VIN lesions demonstrated frequent gains at chromosome 1pq, 3q, 19, and/or 20q . Gains of chromosome 1pq, 3q, and 20q were also common in HPV‐positive anal intraepithelial neoplasia .…”
Section: Discussionsupporting
confidence: 85%
“…In agreement with this, 2 previous studies on HPV-positive VIN lesions demonstrated frequent gains at chromosome 1pq, 3q, 19, and/or 20q. 15,16 Gains of chromosome 1pq, 3q, and 20q were also common in HPV-positive anal intraepithelial neoplasia. 39 The frequent gains of chromosome 1 and 20 and loss of chromosome 4 mentioned above were rarely present in HPV-positive VSCC.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Differences were also seen in comparison of HPV cohorts in oropharyngeal squamous cell carcinomas [ 18 , 44 ], which highlighted Xp gain and 16q loss more common in HPV-positive cases, and 3p, 5q, 9p, 15q and 18q loss more common in HPV-negative cases [ 18 ]. In contrast to these studies, a higher frequency of 1q gain in our HPV-positive cohort is in accordance with HPV-positive VSCCs [ 45 ] and CSCCs [ 46 48 ]. Further analysis by Jung et al .…”
Section: Discussioncontrasting
confidence: 52%